2021
DOI: 10.3389/fonc.2021.631995
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive and Guidance Value of Signet Ring Cell Histology for Stage II/III Colon Cancer Response to Chemotherapy

Abstract: PurposeTo evaluate the predictive and guidance value of signet-ring cell carcinoma for chemotherapy response in stage II/III colon cancer.MethodsEligible patients were recruited from the Surveillance, Epidemiology and End Results (SEER) database. The differences between adenocarcinoma (AD) and SRCC groups in the incidence of patients’ demographic and clinical characteristics were analyzed by Pearson’s chi-squared (×2) test. Survival was analyzed using the Kaplan–Meier method, and the differences were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The most recent systematic evaluation analysis concluded that chemotherapy had different effects on OS in triple-negative breast cancer patients with different tissue subtypes (6). Jiang et al demonstrated that the efficacy of chemotherapy was not statistically significant for signet ring cell cancer (SRCC) and adenocarcinoma (AD) in stage II colon cancer, whereas chemotherapy for stage III SRCC significantly reduced the risk of cancer-specific death (7). Another study found that radiotherapy for urothelial carcinoma improved OS in patients with AD and transitional cell carcinoma, but had no significant effect on squamous cell carcinoma (8).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent systematic evaluation analysis concluded that chemotherapy had different effects on OS in triple-negative breast cancer patients with different tissue subtypes (6). Jiang et al demonstrated that the efficacy of chemotherapy was not statistically significant for signet ring cell cancer (SRCC) and adenocarcinoma (AD) in stage II colon cancer, whereas chemotherapy for stage III SRCC significantly reduced the risk of cancer-specific death (7). Another study found that radiotherapy for urothelial carcinoma improved OS in patients with AD and transitional cell carcinoma, but had no significant effect on squamous cell carcinoma (8).…”
Section: Introductionmentioning
confidence: 99%